JOB LOSS INSURANCE PROGRAM APPLICABLE IN INDONESIA BASED ON GOVERNMENT REGULATION AND ITS COMPARISON WITH OTHER COUNTRIES - Suparto Suparto (Awang Long Law Review, 2023)
One of the regulations in the field of employment issued by the Government of Indonesia is Government Regulation No. 37 of 2021 concerning the Implementation of the Job Loss Insurance Program. This regulation is very important in the midst of rampant layoffs by companies as a result of the Covid-19 pandemic. The purpose of this study was to determine the implementation of a job loss insurance program for employees affected by termination of employment. The research method uses a normative juridical approach with secondary data. Based on the research results obtained that Comparison job loss insurance program in Indonesia with other countries lies in the coverage, requirements and premium contributions. Job loss guarantee or unemployment insurance in Indonesia and other countries have the same goal, which is to financially support individuals who do not have jobs as long as the individual is looking for work. This policy has been carried out since 1935 and 1940 by the United States and Canada against the background of the Great Depression around 1930, then Thailand began to implement an unemployment insurance scheme in 2004. In 2016, there were 73 (seventy-three) countries that had implemented the unemployment insurance scheme. Each country creates an unemployment insurance policy with a different model but the goal remains the same, which is to achieve adequate protection against the risk of job loss by expanding coverage to ensure workers affected by layoffs receive compensation. Based on a comparison with several other countries, it was found that the job loss insurance scheme was effective in overcoming the number of unemployed, especially during an economic recession and was able to protect workers who were laid off by maintaining their level of welfare.